Assessment of sarcopenia in virally suppressed HIV-infected Asians receiving treatment. (15th May 2018) - Abdul Aziz, Siti Azdiah; Mcstea, Megan; Ahmad Bashah, Nor Syuhada; Chong, Meng Li; Ponnampalavanar, Sasheela; Syed Omar, Sharifah Faridah; Sulaiman, Helmi; Azwa, Iskandar; Tan, Maw Pin; Kamarulzaman, Adeeba; Rajasuriar, Reena; Kamaruzzaman, Shahrul Bahyah
Abstract : Objectives: In a clinic-based, treated HIV-infected cohort, we identified individuals with sarcopenia and compared with age, sex and ethnically matched controls; and investigated associated risk factors and health outcomes. Design: Sarcopenia (age-related muscle loss) causes significant morbidity to the elderly, leading to frequent hospitalizations, disability and death. Few have characterized sarcopenia in the HIV-infected who experience accelerated aging. Methods: Sarcopenia was defined as low muscle mass with weak grip strength and/or slow gait speed using lower 20th percentiles of controls. Multivariate logistic and linear regression analyses were used to explore risk factors and health-related outcomes associated with sarcopenia among HIV-infected individuals. Results: We recruited 315 HIV-infected individuals aged at least 25 years with at least 1-year history of undetectable viral load on treatment (HIV RNA <50 copies/ml). Percentage of sarcopenia in 315 HIV-infected was 8%. Subsequently, 153 of the 315 were paired with age, sex and ethnically matched HIV-uninfected. The percentage of sarcopenia in the HIV-infected ( n = 153) compared with uninfected ( n = 153) were 10 vs. 6% ( P = 0.193) respectively, whereas of those at least 50 years of age among them were 17% vs. 4% ( P = 0.049), respectively. Associated risk factors among the HIV-infected include education level, employment status, BMI, baseline CD4 + cell count, duration on NRTIs and GGT levels. Identified negative outcomes include mortality risk scores [5.42; 95% CI 1.46–9.37; P = 0.007) and functional disability (3.95; 95% CI 1.57–9.97; P = 0.004). Conclusion: Sarcopenia is more prevalent in HIV-infected at least 50 years old compared with matched controls. Our findings highlight associations between sarcopenia with loss of independence and greater healthcare burden among treated HIV-infected individuals necessitating early recognition and intervention.